Synthesis of nickel-rubber nanocomposites and evaluation of their dielectric properties - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2009)
Nanocomposites based on natural rubber and nano-sized nickel were synthesized by incorporating nickel nanoparticles in a natural rubber matrix for various loadings of the filler. Structural, morphological, magnetic and mechanical properties of the composites were evaluated along with a detailed study of dielectric properties. It was found that nickel particles were uniformly distributed in the matrix without agglomeration resulting ill a magnetic nanocomposite. The elastic properties showed an improvement with increase in filler content but breaking stress and breaking strain were found to decrease. Dielectric permittivity was found to decrease with increase in frequency, and found to increase with increase in nickel loading. The decrease in permittivity with temperature is attributed to the high volume expansivity of rubber at elevated temperatures. Dielectric loss of blank rubber as well as the composites was found to increase with temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dielectric relaxation; Interfacial polarization; Nanocomposites

Flexible microwave absorber based on nickel ferrite nanocomposite - Sunny, Vijutha; Kurian, Philip; Mohanan, P.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2010)
Flexible magnetic composite materials were prepared by incorporating precharacterized nickel ferrite nanoparticles in a natural rubber matrix. The complex dielectric permittivity and magnetic permeability of the composites were measured at different microwave frequencies using the cavity perturbation technique. A steady increase in dielectric permittivity was observed with increase in filler concentration. Maxwell-Garnett mixture equations were employed to model the effective permittivity and permeability of the composite. Reflection loss was estimated by employing the model of single layer absorber backed with a perfect conductor. Reflection loss minima of -5.9 dB at 3.2 GHz for 12 mm thick rubber ferrite composite sheet is obtained in the S-band while a loss up to -16 dB could be achieved at 9.5 GHz in the X-band. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Cavity perturbation; Complex permeability; Complex permittivity; Microwave absorber; Nanocomposites; Nickel ferrite

On the magnetic, mechanical and rheological properties of rubber-nickel nanocomposites - Jamal, E. Muhammad Abdul; Joy, Pattayil Alias; Kurian, Philip; Anantharaman, Maliemadom R. (Polymer Bulletin, 2010)
Rubber-nickel nanocomposites were synthesized by incorporating freshly prepared nanometric nickel particles in two different matrices namely natural rubber and neoprene rubber according to specific recipes for various loadings of nano nickel and the cure characteristics of these composites were evaluated. The maximum torque values register an increase with the increase in loading of nickel in both composites and this is attributed to the non-interacting nature of nickel nanoparticles with rubber matrices. The cure time of natural rubber composites decreases with increase in the content of nickel, and in neoprene rubber cure, time increases with increase in filler content. In natural rubber, the curing reaction seems to be activated by the presence of nickel particles. The magnetization studies of the composites reveal that the magnetic properties of nickel are retained in the composite samples. The elastic modulus of natural rubber and neoprene rubber are largely improved by the incorporation of nickel particles.
Keywords: Cure characteristics; Elastic modulus; magnetic properties; Nanocomposites